STUDY MOLECULES DOCKING OF ALKALOIDS IN KRATOM ON SEROTONIN TRANSPORTER (SERT), NOREPINEPHRINE TRANSPORTER (NET), AND MONOAMINE OXIDASE (MAO) - Irawan, Dandi; Wijianto, Bambang; IH, Hariyanto (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Kratom (Mitragyna speciosa Korth) is a tropical plant originating from Southeast Asia that predominantly contains alkaloid compounds and can potentially maintain levels of monoamine compounds in the body to treat depression. The study aimed to examine the potential of 8 alkaloid compounds in kratom as antidepressants towards four target proteins: Serotonin Transporter (SERT), Dopamine Transporter (DOPAT), Leucine Transporter (LEUT), and Monoamine Oxidase (MAO) via molecular docking. The Pyrx program is used with exhaustiveness 106 as the protocol, and the grid is adapted to the active site of each receptor. The affinity values